The city sings green : & other poems about welcoming wildlife - Silverman, Erica (Clarion Books, an imprint of HarperCollins Publishers, 2024)
A unique and artful blend of poetry, science, and activism, this picture book shows how city dwellers can intervene so that nature can work her magic. Perfect for fans of The Curious Garden and Harlem Grown.